Voleibol na adolescência e o desenvolvimento do autodomínio emocional: dilemas dos contextos curriculares e extracurriculares na ação pedagógica do professor de educação física - Oliveira, Alessandra Weiss Ferraz de (2019)
Sport has been a means to develop individuals' emotional and social control. Over the years, man has realized that sport can result in a pleasant mimetic excitement, which balances tensions linked to day-to-day stress and becomes a fundamental part of social survival. From an early age, the subject learns to model his emotions according to the code of social conduct that becomes the constituent element of his personality. Thus, the formation of the psychic apparatus continues during adolescence, the stage of life that the subject presents oscillations of behavior and tends to be susceptible to the intercurrences of the environment. Thus, working with adolescence in sport seems to be fundamental for the maturation of the emotional aptitudes of empathy and selfcontrol, responsible for the development of emotional self-mastery. The objective of this dissertation was to analyze whether physical education teachers, during the teaching-learning process of volleyball in the curricular and extracurricular axis, provide the development of emotional self-mastery of adolescent students. The methodology used has qualitative, descriptive and comparative characteristics. A semi-structured interview was conducted with 4 main topics and 4 secondary topics, with 12 Physical Education teachers working in public schools of elementary education II and in the sports and leisure departments of Curitiba, specifically teachers of the Municipal Education Network and teachers of the Municipal Youth Sports and Recreation Department (SMELJ) involved in the School + Sport Program = 10 (EE10). To analyze the data, we used the content analysis of Bogdan and Biklen (1994), Elias's Theory of the Civilizing Process (1993; 2011) and Goleman's Emotional Intelligence theory (2007; 2012). In the coding process the data transcription was performed in the ATLAS.TI software, version 6.2, in families. Subsequently, we selected 108 speeches that presented mentions of the teaching methodological practice, highlighting only 16 that were compatible with the 12 codes of analysis. The other 92 discourses, which distanced themselves from the codes, were analyzed and discussed from the theoretical background, relating the discourse of practice with theory. We conclude that most of the speeches mentioned pedagogical procedures aimed at empathy, that is, the capacity to understand the emotions of the next; few reports have dealt with the understanding of one's own emotions, self-control. The 92 references of the teaching practice dealt with situations related only to the technical context and content, failing to explore other important characteristics of the integral formation of the subject. Although there were actions and tasks aimed at the emotional formation of the student, the teachers demonstrated in their methodological procedures lack of preparation or lack of knowledge about working with emotions.